Photosystem II monomeric antenna CP26 plays a key role in nonphotochemical quenching in Chlamydomonas - Cazzaniga, Stefano; Kim, Minjae; Pivato, Matteo; Perozeni, Federico; Sardar, Samim; D’Andrea, Cosimo; Jin, EonSeon; Ballottari, Matteo (Plant physiology (Bethesda), 2023)
Abstract Thermal dissipation of excess excitation energy, called nonphotochemical quenching (NPQ), is 1 of the main photoprotective mechanisms in oxygenic photosynthetic organisms. Here, we investigated the function of the monomeric photosystem II (PSII) antenna protein CP26 in photoprotection and light harvesting in Chlamydomonas reinhardtii, a model organism for green algae. We used CRISPR/Cas9 genome editing and complementation to generate cp26 knockout mutants (named k6#) that did not negatively affect CP29 accumulation, which differed from previous cp26 mutants, allowing us to compare mutants specifically deprived of CP26, CP29, or both. The absence of CP26 partially affected PSII activity, causing reduced growth at low or medium light but not at high irradiances. However, the main phenotype observed in k6# mutants was a more than 70% reduction of NPQ compared to the wild type (Wt). This phenotype was fully rescued by genetic complementation and complemented strains accumulating different levels of CP26, demonstrating that ∼50% of CP26 content, compared to the Wt, was sufficient to restore the NPQ capacity. Our findings demonstrate a pivotal role for CP26 in NPQ induction, while CP29 is crucial for PSII activity. The genetic engineering of these 2 proteins could be a promising strategy to regulate the photosynthetic efficiency of microalgae under different light regimes. Targeted mutagenesis and complementation in Chlamydomonas reveal the functions of CP26, a monomeric antenna of photosystem II, demonstrating its key role in regulating photoprotection.